Peran Organisasi Petani dalam Mengoptimalkan Kinerja Rantai Pasok dan Pembentukan Nilai Tambah Kakao: Studi Kasus di Kabupaten Kolaka, Sulawesi Tenggara - Abdul Muis Hasibuan; Agus Wahyudi; Dewi Listyati; Asif Aunillah; Ermiati Ermiati; Maman Herman (Pusat Penelitian dan Pengembangan Perkebunan, 2015)
Cultivation of cocoa in Indonesia is dominated by small farmers who have not been well organized, so they usually marginalized in the cocoa agribusiness systems. This study aimed to analyze the role of farmer organizations in an effort to optimize the performance of the cocoa supply chain and value addition in cocoa value chain system. The research was conducted in Kolaka, Southeast Sulawesi from February to October 2012. The collected data is primary and secondary data by conducting in-depth interviews to farmers/farmer groups, traders and exporters/industry. All of the data and information were analyzed by supply chain approach and added value. The results showed that the condition of farmers' organizations in Kolaka very diverse and can be grouped into four models according to the activity and its role in the supply chain and value addition of cocoa beans. Farmer organizations led by Model A was able to give farmers a better share than others, i.e. 99.43% for fermented cocoa bean and 96.92% for unfermented. Similarly, added value for farmers were IDR509.00/kg for fermented cocoa beans and IDR1,019.00/kg for unfermented. Therefore, farmers' organizations need to be directed to be more efficient on cocoa beans distribution and marketing that create a well performance of supply chain system and provide added value to the farmer.